Pelatihan dan Pendampingan Guru SMP Muhammadiyah 3 Kepanjen dalam Mengembangkan Media Pembelajaran Berbasis Literasi Numerasi: Training and Assistance for Muhammadiyah 3 Kepanjen Middle School Teachers in Developing Numeracy Literacy-Based Learning Media - Effendi, Moh. Mahfud; Cahyono, Hendarto; Ummah, Siti Khoiruli (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This community service program aims to train and assist teachers in creating numeracy literacy-based learning media. The characteristics of this media are that it contains content, context, and types of Minimum Competency Assessment (AKM) questions. This is motivated by the implementation of the Merdeka Curriculum which is based on numeracy literacy which is not yet optimal. The implementation method is training and mentoring by a lecturer service team and a community service team by students (PMM Mitra Lecturer) targeting teachers at Muhammadiyah 3 Kepanjen Middle School. The success of this service program is the creation of learning media that includes the concept of numeracy literacy. The results of the training and mentoring that have been carried out are the formation of learning media within the context of literacy activities and connections between subjects. It should be noted that previously teachers had never created learning media so learning at school used the 2013 Curriculum student books. All of this learning media was developed using PowerPoint. The next recommendation for the community service program is teacher assistance in creating AKM-type questions.